Early medieval fortified settlements of the Pomeranian-Kuyavia limesis – archaeology and conservation issues - Bojarski, Jacek; Chudziak, Wojciech; Dygaszewicz, Elżbieta (Archaeologia Historica Polona, 2022)
The text discusses three different cases of rescue research carried out in recent years by the Institute of Archaeology the Nicolaus Copernicus University in Toruń on fortified settlements in Bydgoszcz-Stare Miasto, Pawłówek and Bydgoszcz-Fordon (historic Wyszogród), in the Kujawsko-Pomorskie voivodeship. These settlements played an important role in the early Middle Ages as centres of exchange and defence of the Greater Poland-Kuyavia borderland. Together with their immediate settlement base, they were subject to destruction processes to varying degrees. These destructions were the result of natural and human activities. The progressive degradation required wide-ranging archaeological investigations to be carried out on these sites and appropriate legal, administrative and conservation measures to be taken in order to secure the remaining relics.